Regulation of transcription by ubiquitin and the INO80 chromatin remodeling complex - Ndoja, Ada, author; Yao, Tingting, advisor; Cohen, Robert, advisor; Stargell, Laurie, committee member; Hansen, Jeffrey, committee member; Wilusz, Carol, committee member (Colorado State University. Libraries, 2015)
Transcription in eukaryotes is a crucial process that is tightly regulated in order to maintain cellular homeostasis and offer optimal responses to environmental changes. Transcriptional activators (TAs) regulate this process by orchestrating time and locus-specific assembly of complex transcription machinery. Thus, the abundance, localization and activity of TAs are all subject to tight control. One way in which TAs are controlled is by the covalent attachment of the conserved protein ubiquitin. Ubiquitination of TAs has been reported to affect transcription via proteolytic and non-proteolytic routes, yet the function of the ubiquitin signal in the non-proteolytic process is poorly understood. Through studies of a series of synthetic and natural activators in yeast and mammalian cells, we found that mono-ubiquitinated TAs cannot stably interact with DNA to promote transcription. We have identified the AAA+ ATPase Cdc48 and its cofactors as the Ub receptor responsible for extracting mono-ubiquitinated activators from chromatin, independently of proteolysis. These findings describe a novel mechanism by which gene repression can be maintained without destroying the activator. Upon appropriate stimulus, deubiquitinating enzymes can readily reverse mono- or oligo-ubiquitination of the activator and transcription can initiate without the requirement for new protein synthesis. This mechanism may facilitate rapid switching between “on” and “off” states of transcription and may serve as a general strategy to prevent spurious transcription in the “off” state. Compaction of DNA into chromatin imparts further layers of complexity to the control of eukaryotic gene expression. Cooperation between chromatin remodelers, histone variants, and histone post-translational modifications (PTMs) offers diverse regulatory options in DNA metabolic processes, including transcription and DNA repair. The human INO80 chromatin-remodeling complex (hINO80) has been shown to facilitate transcription by promoting an open chromatin environment at promoter regions. How and whether hINO80 directly promotes an open chromatin environment is not yet understood. In an effort to elucidate how hINO80 regulates transcription, we have characterized the nucleosome sliding activity of hINO80 and examined how histone variant H2A.Z and histone PTMs modulate its activity in vitro. Our results suggest that nucleosomes containing H2A.Z or the H3 acetylation mimic, K56Q, are mobilized by hINO80 with faster kinetics compared to canonical unmodified nucleosomes, and their effects are additive. In contrast, ubiquitination of H2A or H2B does not affect the sliding activity of hINO80. Nucleosomes containing both H2A.Z and H3-K56Ac are enriched at promoter regions and DNA damage sites in mammalian cells. These nucleosomes have been shown to exhibit rapid turnover kinetics in vivo. Our studies provide biochemical evidence that hINO80 participates in transcription and DNA repair processes by ATP-dependent mobilization of H2A.Z/H3-K56Ac-containing nucleosomes. Future studies will be required to elucidate how nucleosome mobilization in vitro relates to chromatin dynamics in vivo.
Keywords: remodeler; ubiquitin; transcription; chromatin